PENGARUH PUPUK ORGANIK CAIR (POC) LIMBAH PASAR TERHADAP PRODUKSI TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) DI GREEN HOUSE FMIPA UPG 1945 NTT - Meliana Sari Wati Kaseh; Maya F. Roman; Nardi Matias Leo; Nur Aini Bunyani (CV. ADIBA AISHA AMIRA, 2026)
This study aimed to determine the effect of market waste-based liquid organic fertilizer (LOF) on the growth and production of water spinach (Ipomoea reptans Poir), as well as to determine the best concentration for optimal results. The study was conducted at the Green House of FMIPA UPG 1945 NTT, Oebobo District, Kupang City, East Nusa Tenggara, from November 2025 to January 2026 using a Randomized Block Design (RBD) consisting of five treatments and five replications. The treatments consisted of P0 (control), P1 (25 ml/L water), P2 (50 ml/L water), P3 (75 ml/L water), and P4 (100 ml/L water). The observed variables included plant height, leaf length, number of leaves, and fresh weight. Data were analyzed using Analysis of Variance (ANOVA) followed by the Least Significant Difference (LSD) test at a 5% significance level. The results showed that the application of market waste-based liquid organic fertilizer had a highly significant effect on all growth and production parameters of water spinach. The best treatment was obtained in P4 (100 ml/L water), resulting in the highest plant height (36.4 cm), leaf length (15 cm), number of leaves (11.8 leaves), and fresh weight (3.12 g). Therefore, market waste-based liquid organic fertilizer is effective in improving the growth and production of water spinach and has the potential to become an environmentally friendly and economical fertilizer alternative.